Study of the influence of vacuum-arc coating on the wear-resistance of piston rings - Glushkova, D.; Глушкова, Діана Борисівна (Харківський національний автомобільно-дорожній університет, 2021)
The effect of a multilayer vacuum-arc nanostructured Ti-Mo-N coating, its application parameters on the wear resistance of piston rings is studied. The effect of the parameters of vacuum-arc deposition on the nanohardness is established.
Дослідження впливу вакуумно-дугового покриття на зносостійкість поршневих кілець
Keywords: vacuum-ars settling; anohardness; wear-resistant; piston rings; покриття; нанотвердість; зносостійкість; поршневі кільця; 669.017; 10.30977/BUL.2219-5548.2021.94.0.59